1990
DOI: 10.1115/1.2920277
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Multilevel Solution of the EHL Line Contact Problem

Abstract: The application of multilevel multi-integration to the calculation of the elastic deformation integrals and the use of an alternative relaxation process in the multilevel solution of the governing equations have resulted in an algorithm solving the EHL line contact problem in O(n ln n) operations, also for highly loaded situations. The reduction in computing time thus obtained was used to solve the problem using large numbers of nodal points and to study the pressure spike. The presented algorithm will enable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
292
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(302 citation statements)
references
References 10 publications
(27 reference statements)
6
292
0
4
Order By: Relevance
“…Results indicated the effect of squeeze in the response in which there was some deviation from exact periodicity in the cavitation location, contact separation and minimum film thickness under the dynamic loading imposed. Minimum film thickness calculations demonstrated that the ALE formulation accurately describes the EHL response established in the literature [9,10,[50][51][52] to within 5% of the predicted values. It was also presented under hydrodynamic conditions that the ALE formulation has better numerical converge and computes in less time than comparative problems solved using the Elrod (Heaviside) approach.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Results indicated the effect of squeeze in the response in which there was some deviation from exact periodicity in the cavitation location, contact separation and minimum film thickness under the dynamic loading imposed. Minimum film thickness calculations demonstrated that the ALE formulation accurately describes the EHL response established in the literature [9,10,[50][51][52] to within 5% of the predicted values. It was also presented under hydrodynamic conditions that the ALE formulation has better numerical converge and computes in less time than comparative problems solved using the Elrod (Heaviside) approach.…”
Section: Discussionmentioning
confidence: 98%
“…Later Lubrecht et al [52] derived a solution based on the multilevel methods and Moe's non-dimensional parameters. This was further developed by Venner [10] who derived an expression that is considered the best approximation for calculating the minimum film thickness in a line contact to date. It is of note that, despite the differences in model assumptions, the solutions obtained by Dowson and Higginson [9] are widely used because of the accuracy of the solution when comparing to the modern alternatives [53].…”
Section: Investigation Of the Minimum Film Thicknessmentioning
confidence: 99%
See 2 more Smart Citations
“…The Reynolds equation was solved by a multi-grid (MG) method, while the elastic deformation was calculated using a multi-level multi-integration (MLMI) technique (Gao et al, 2007;Venner, 1991). Three levels of grid were used in the multilevel solver.…”
Section: Elastohydrodynamic Lubricationmentioning
confidence: 99%